Scaleable processes for the synthesis of (−)-β-D-2,6-diaminopurine dioxolane (Amdoxovir, DAPD) and (−)-β-D-2-aminopurine dioxolane (APD) - Zhou, Longhu (2012)
An efficient and scalable synthesis of (−)-DAPD and (−)-APD has been developed. We discovered that t-butyl cyanoacetate can be used as a new additive for the sugar nucleoside base coupling step en route to DAPD with improved β-selectivity and an isolated yield four fold greater than the original process scale method. Using this new process, (−)-DAPD has been prepared on greater than 20 g scale. In the synthesis of (−)-APD, a key enzyme-catalyzed hydrolysis reaction afforded the water-soluble deprotected α-anomer while leaving the β-anomer completely untouched.